FIRST RECORD OF NON-NATIVE LORICARIID CATFISH, PTERYGOPLICHTHYS DISJUNCTIVUS (WEBER, 1991) (SILURIFORMES, LORICARIIDAE) IN CAUVERY RIVER OF PENINSULAR INDIA - PREETHA PANIKKAR,; T. D. JAGADEESH,; D. S. KRISHNA RAO,; U. K. SARKAR,; M. NASKAR, (The Bioscan, 2015)
Cauvery is an important river of Peninsular India and is home to a number of endemic species. This report provides the first record of the Sucker mouth armoured catfish Pterygoplichthys disjunctivus, belonging to the family Loricariidae, from river Cauvery. The fish was collected at Sathegala stretch of river Cauvery (12 0 15 ' 13"N and 77 0 09’38"S). Aquarium trade has been responsible for the introduction of many alien species including catfishes of the genus Pterygoplichthys to many countries including India. These catfishes have been considered as invaders worldwide. Their occurrence in the wild may be probably due to escape from culture ponds and unintentional releases to the wild. The establishment and uncontrolled spread of P. disjunctivus may be a threat to freshwater faunal diversity of river Cauvery, if preventive measures are not immediately put in place.